The existence of Tanah Liek Batik in the development of creative industries in Padang City - Rosalena Aprizia; Agusti Efi (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
Tanah Liek Batik is a distinctive Minangkabau textile that uses natural clay-based dyes and holds deep historical and philosophical meaning. This study examines the existence and sustainability of Tanah Liek Batik within Padang's creative sector and evaluates the government’s role in supporting its development. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model, encompassing data reduction, display, and conclusion drawing. The findings introduce a new perspective by positioning Tanah Liek Batik not only as a traditional craft but also as an adaptive cultural industry that integrates heritage preservation with modern entrepreneurial strategies. The findings reveal that Tanah Liek Batik serves as both a marker of Minangkabau cultural identity and an economic commodity that contributes to employment, local income, and tourism. Entrepreneurs maintain their relevance through motif innovation, product diversification, and digital marketing. The novelty of this research lies in identifying the dynamic transformation of Tanah Liek Batik from a local cultural product into a creative economic asset through digital adaptation and intergenerational collaboration. However, challenges persist, including limited market access, high production costs, scarcity of raw materials, competition from printed batik, and low interest among youth. Government agencies have supported artisans through training, funding, equipment provision, and promotion, though constrained by limited budgets and weak regeneration. The study highlights the need for culture-based innovation and stronger youth involvement to ensure the sustainability of this traditional Minangkabau craft.   Batik Tanah Liek merupakan tekstil khas Minangkabau yang menggunakan pewarna alami berbasis tanah liat serta memiliki makna historis dan filosofis yang mendalam. Penelitian ini menganalisis eksistensi dan keberlanjutan Batik Tanah Liek dalam sektor industri kreatif di Kota Padang serta mengevaluasi peran pemerintah dalam mendukung pengembangannya. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui wawancara, observasi, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman yang mencakup reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian ini memperkenalkan perspektif baru dengan memposisikan Batik Tanah Liek tidak hanya sebagai kerajinan tradisional, tetapi juga sebagai industri budaya adaptif yang mengintegrasikan pelestarian warisan dengan strategi kewirausahaan modern. Hasil penelitian menunjukkan bahwa Batik Tanah Liek berperan sebagai penanda identitas budaya Minangkabau sekaligus sebagai komoditas ekonomi yang berkontribusi terhadap lapangan kerja, pendapatan daerah, dan pariwisata. Para pelaku usaha menjaga relevansinya melalui inovasi motif, diversifikasi produk, dan pemasaran digital. Kebaruan penelitian ini terletak pada identifikasi perubahan Batik Tanah Liek dari produk budaya lokal menjadi aset ekonomi kreatif melalui adaptasi digital dan kolaborasi antar generasi. Namun, tantangan tetap ada, seperti keterbatasan akses pasar, tingginya biaya produksi, kelangkaan bahan baku, persaingan dengan batik cap, serta rendahnya minat generasi muda. Pemerintah telah memberikan dukungan kepada para perajin melalui pelatihan, pendanaan, bantuan peralatan, dan promosi, meskipun masih terkendala oleh keterbatasan anggaran dan lemahnya regenerasi. Penelitian ini menegaskan pentingnya inovasi berbasis budaya dan keterlibatan generasi muda untuk menjaga keberlanjutan kerajinan tradisional Minangkabau ini.